2004
DOI: 10.1159/000080330
|View full text |Cite
|
Sign up to set email alerts
|

ClC-3-independent, PKC-dependent Activity of Volume-sensitive Cl<sup>-</sup> Channel in Mouse Ventricular Cardiomyocytes

Abstract: Volume-sensitive outwardly rectifying (VSOR) Cl- channels are activated during osmotic swelling and involved in the subsequent volume regulation in most animal cells. To test the hypothesis that the ClC-3 protein is the molecular entity corresponding to the VSOR Cl- channel in cardiomyocytes, the properties of VSOR Cl- currents in single ventricular myocytes isolated from ClC-3-deficient (Clcn3-/-) mice were compared with those of the same currents in ClC-3-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 51 publications
(75 reference statements)
8
40
0
Order By: Relevance
“…This difference may be related to the relative amounts of ClC-3 and ICl swell protein that are inserted into the plasma membrane in these two cell types at any one time. Activation of ICl swell by ClC-3 overexpression alone is consistent with previous work, demonstrating that in these same murine VSM cells, Ad-ClC-3 expression alone enhances H 2 O 2 -dependent NF-B activation, even in the absence of other stimuli (21 (15)(16)(17), the size of the ICl swell elicited by hypotonic conditions was not altered in ClC-3 null VSM cells (Fig. 4).…”
Section: Reduction Of Extracellular CLsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference may be related to the relative amounts of ClC-3 and ICl swell protein that are inserted into the plasma membrane in these two cell types at any one time. Activation of ICl swell by ClC-3 overexpression alone is consistent with previous work, demonstrating that in these same murine VSM cells, Ad-ClC-3 expression alone enhances H 2 O 2 -dependent NF-B activation, even in the absence of other stimuli (21 (15)(16)(17), the size of the ICl swell elicited by hypotonic conditions was not altered in ClC-3 null VSM cells (Fig. 4).…”
Section: Reduction Of Extracellular CLsupporting
confidence: 91%
“…Unfortunately, other investigators have either been unable to express ClC-3 currents (8 -10) or have observed currents that were insensitive to changes in cell volume (10 -14). Importantly, ClC-3 null cells have consistently exhibited normal appearing whole-cell (15)(16)(17) and single channel (18) ICl swell currents. The regulation of ICl swell was, however, clearly altered in ClC-3 null cells (6).…”
mentioning
confidence: 99%
“…I Cl,Ca (9,11,24) requires an elevation of [Ca 2ϩ ] i for its activation. I Cl,vol (8,9,11,29) exhibits a time-dependent inactivation at positive potentials and is sensitive to both DIDS and tamoxifen. I Cl,CFTR (9,11) shows little rectification under symmetrical [Cl Ϫ ] conditions and is insensitive to DIDS.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested to mediate swelling-activated Cl Ϫ currents (Duan et al, 1997) or (different) Ca 2ϩ -activated Cl Ϫ currents Wang et al, 2006) in plasma membranes. Clcn3 Ϫ/Ϫ mice lacked neither current (Stobrawa et al, 2001;Arreola et al, 2002;Gong et al, 2004). ClC-3 was also proposed to have roles in neutrophil and smooth muscle reactive oxygen species generation (Moreland et al, 2006;Miller et al, 2007) and in ␤ cell insulin secretion (Barg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%